Political Ambiguity and Confessional Diversity in the Funeral Processions of Stadholders in the Dutch Republic - Janssen, Geert H. (The sixteenth century journal, 2009)
This article explores how the funeral processions of the Dutch stadholders negotiated the ambiguous outcomes of the Dutch Revolt and the Reformation. Basing themselves on the obsequies of the former Habsburg sovereigns, the directors of these public ceremonies created a separation between the private and public identities of the deceased. This was important since the sovereignty of the republican Dutch state was no longer involved in the symbolic transfer of dynastic powers to a new heir. The first part of the parade was therefore marked by symbols referring to the private possessions of the family of Orange-Nassau, whereas in the second, public section members of republican institutions participated. Religiously, the funeral processions reveal a program which was deliberately nonconfessional, in order to transcend religious divisions in Dutch society.